2016
DOI: 10.1002/anie.201603385
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Catalyzed Modular Synthesis of Cyclic Tertiary Amines from Lactams

Abstract: Reported is the development of a novel catalytic cascade reaction facilitating the modular synthesis of cyclic tertiary amines from simple lactam substrates and secondary alcohols. Using a single molecular ruthenium-triphos catalyst in the presence of molecular hydrogen enabled the versatile formation of various amines in high yield with excellent selectivity. Extending the reaction system to using an alcohol as the hydrogen transfer reagent allowed the reduction of lactams without the need for molecular hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…On the other hand, such two-step mechanism was further confirmed and applied by Klankermayer and co-workers for the synthesis of cyclic tertiary amines from lactams and alcohols in the presence of [Ru(Triphos-xyl)(tmm)] complex and MSA ( Fig. 3d) 61 . Moreover, the authors showed that the lactam can be hydrogenate/N-alkylated even with the absence of molecular hydrogen, just by using an alcohol as hydrogen transfer reagent 61 .…”
Section: Development Of Homogeneous Catalystssupporting
confidence: 62%
“…On the other hand, such two-step mechanism was further confirmed and applied by Klankermayer and co-workers for the synthesis of cyclic tertiary amines from lactams and alcohols in the presence of [Ru(Triphos-xyl)(tmm)] complex and MSA ( Fig. 3d) 61 . Moreover, the authors showed that the lactam can be hydrogenate/N-alkylated even with the absence of molecular hydrogen, just by using an alcohol as hydrogen transfer reagent 61 .…”
Section: Development Of Homogeneous Catalystssupporting
confidence: 62%
“…Recently, effective molecular catalysts for the reduction of challenging functionalities could be developed, exemplified by the highly versatile and stable ruthenium complex [Ru(triphos)tmm] [ A , triphos = (1,1,1-tri(diphenylphosphinomethyl)ethane, tmm = trimethylenemethane] as privileged system. This important advancement moved this molecular catalyst, and especially recently optimized catalyst structure [Ru(triphos-xyl)tmm] [ B , triphos-xyl=1,1,1-tri(bis(3,5-dimethylphenyl)phosphinomethyl)ethane], into the spotlight for novel transformations and in special cases closer to the harsher processing conditions of heterogeneous catalyst systems ( 20 , 21 ). Consequently, the application of these systems in the challenging transformation of robust and stable polymeric materials was envisaged, using molecular hydrogen for the respective hydrogenolysis reaction.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Hydrogenation of NH lactams can give N-heterocycles, 14 , 19 with alkylation of the N atom if the reactions are carried out in alcohols. 20 A simple route involving the hydrogenation of dicarboxylic acid derivatives in the presence of an amine ( Scheme 1 ) would represent a step change in the synthesis of N-heterocycles.…”
Section: Introductionmentioning
confidence: 99%